MICROFACIES AND MICROFOSSIL ASSEMBLAGES (SMALLER FORAMINIFERS, ALGAE, PSEUDOALGAE) OF THE HUECO GROUP AND LABORCITA FORMATION (UPPER PENNSYLVANIAN-LOWER PERMIAN) SOUTH-CENTRAL NEW MEXICO, USA (Rivista italiana di Paleontologia e Stratigrafia, 2003)
During the latest Carboniferous and earliest Permian (Virgilian-Wolfcampian), the eastern margin of the Orogrande Basin in south-central New Mexico was rimmed by a narrow, tectonically unstable shelf, on which sediments of the Laborcita and Abo formations were deposited. Sediments of the Hueco Group accumulated on the more stable western margin of the Orogrande Basin. On the eastern shelf, the Laborcita Formation of the northern Sacramento Mountains represents a transition from marine to terrestrial facies and is composed of clastic-carbonate cycles. Limestones accumulated during relative sea-level highstands in a shallow marine shelf environment. Clastic sediments were deposited during relative lowstands when there was strong clastic influx in a nearshore to terrestrial environment. The overlying Abo Formation is composed of terrestrial red beds. On the western shelf, the Shalem Colony Formation of the Hueco Group, equivalent to the Laborcita Formation, is composed of mostly normal marine shallow shelf limestones with only minor interbedded clastics. The Robledo Mountains Formation and Hueco Group reflects a trend from a restricted shallow  shelf and tidal flat clastics facies in the lower part to more open conditions in the upper part, which also prevailed during deposition of the overlying Apache Dam Formation. Limestones of the Laborcita Formation and Hueco Group contain smaller foraminifers, algae and problematic carbonate microfossils. All taxa except two pseudoalgae in open nomenclature (Litostroma (?) sp. and “problematicum gen. 1”) are taxa already described. Compared with the Carnic Alps (Austria/Italy), the assemblages of smaller foraminifers of the Laborcita Formation  and Shalem Colony Formation are very similar to those of the Auernig and Carnizza Formations (Auernig Group), and Lower Pseudoschwagerina Limestone (Rattendorf Group), indicating an Orenbugian (“Bursumian”) to Asselian age. Smaller foraminifers of the Robledo Mountains Formation allow correlation with the Grenzland Formation and Upper Pseudoschwagerina Limestone (Rattendorf Group) of the Carnic Alps, dated as Asselian to Sakmarian. Smaller foraminifers of the Apache Dam Formation suggest an Artinskian age, correlating with the Wolfcampian, or the Trogkofel Group of the Carnic Alps.